Digital Etiquette for Dummies - Butow, Eric (John Wiley & Sons, Inc., 2022)
Mind your online P's and Q's with this expert digital manners guide Conducting yourself online can be challenging. It sometimes seems like the web and social media is tailor-made to cause upset and anger. But, with the right guide, anyone can learn how to be a beacon of civility and politeness online. In Digital Etiquette For Dummies, a team of online communication experts share their combined insights into improving your presence on social media, writing emails that exude positivity and clarity, behaving correctly in virtual meetings, and much more. You'll become a paragon of politeness as you learn to apply the timeless rules of etiquette to the unique environment of the web, social media, email, Zoom, and smartphones. In this book, you'll also: Learn near-universal etiquette rules for email, social media, cellphones, and more Discover ways to make sure that your polite attitude isn't being lost in the text-only context of a business email Avoid common social media pitfalls and digital faux pas that can trip up even the most careful communicators A great handbook for anyone who uses digital communication in business or in their personal life (so, pretty much everyone), Digital Etiquette For Dummies also belongs on the reading lists of those trying to improve their online interactions on social media.